Second cancers in MPN: Survival analysis from an international study - Marchetti, Monia; Ghirardi, Arianna; Masciulli, Arianna; Carobbio, Alessandra; Palandri, Francesca; Vianelli, Nicola; Rossi, Elena; Betti, Silvia; Di Veroli, Ambra; Iurlo, Alessandra; Cattaneo, Daniele; Finazzi, Guido; et al. (American journal of hematology, 2020)
One out of ten patients with Philadelphia-negative myeloproliferative neoplasms (MPN) develop a second cancer (SC): in such patients we aimed at assessing the survival impact of SC itself and of MPN-specific therapies. Data were therefore extracted from an international nested case-control study, recruiting 798 patients with SC diagnosed concurrently or after the MPN. Overall, 2995 person-years (PYs) were accumulated and mortality rate (MR) since SC diagnosis was 5.9 (5.1-6.9) deaths for every 100 PYs. A "poor prognosis" SC (stomach, esophagus, liver, pancreas, lung, ovary, head-and-neck or nervous system, osteosarcomas, multiple myeloma, aggressive lymphoma, acute leukemia) was reported in 26.3% of the patients and was the cause of death in 65% of them (MR 11.0/100 PYs). In contrast, patients with a "non-poor prognosis" SC (NPPSC) incurred a MR of 4.6/100 PYs: 31% of the deaths were attributed to SC and 15% to MPN evolution. At multivariable analysis, death after SC diagnosis was independently predicted (HR and 95% CI) by patient age greater than 70 years (2.68; 1.88-3.81), the SC prognostic group (2.57; 1.86-3.55), SC relapse (1.53; 10.6-2.21), MPN evolution (2.72; 1.84-4.02), anemia at SC diagnosis (2.32; 1.49-3.59), exposure to hydroxyurea (1.89; 1.26-2.85) and to ruxolitinib (3.63; 1.97-6.71). Aspirin was protective for patients with a NPPSC (0.60; 0.38-0.95). In conclusion, SC is a relevant cause of death competing with MPN evolution. Prospective data are awaited to confirm the role of cytoreductive and anti-platelet drugs in modulating patient survival after the occurrence of a SC.
Keywords: senioři; myeloproliferativní poruchy; hematologické nádory; Male; Middle Aged; Hematologic Neoplasms; mužské pohlaví; studie případů a kontrol; míra přežití; Follow-Up Studies; Myeloproliferative Disorders; věkové faktory; následné studie; Disease-Free Survival; ženské pohlaví; Humans; sekundární malignity; Survival Rate; lidé středního věku; Age Factors; Female; Aged; přežití bez známek nemoci; lidé; Case-Control Studies; Neoplasms, Second Primary